UJI MACAM PUPUK ORGANIK TERHADAP PERTUMBUHAN DAN HASIL 2 VARIETAS TANAMAN STEVIA (Stevia rebaudiana Bertonii M) - Futta Ifnu Guzali; Dewi Ratna Nurhayati; Siswadi Siswadi (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2020)
Research on Organic Fertilizer Tests on Growth and Yield of 2 Stevia Plant Varieties (Stevia rebaudiana Bertonii M)